Long-term vs short-term tocolysis with ritodrine hydrochloride: Propensity score-matched analysis. (March 2023) - Okuda, Akiko; Inayama, Yoshihide; Mizuno, Kayoko; Takeuchi, Masato; Kawakami, Koji; Mandai, Masaki; Higuchi, Toshihiro
Highlights: In Japan, the frequency of preterm birth is lower compared with elsewhere. The treatment for preterm labour in Japan is commonly long-term tocolysis with ritodrine hydrochloride. The treatment for preterm labour in Europe and the USA is short-term tocolysis. We compared long-term and short-term tocolysis protocols for preterm labour. A long-term tocolysis protocol does not contribute to lower frequency of preterm birth. Abstract: Objective: To investigate whether the short-term tocolysis protocol is as effective as the traditional long-term tocolysis protocol with intravenous ritodrine hydrochloride for preterm labour. Study design: This single-centre, retrospective, observational study was conducted at Kitano Hospital, Osaka, Japan between April 2016 and July 2021. At the study hospital, the management protocol for preterm labour after 26 weeks of gestation was changed from the long-term tocolysis protocol to the short-term tocolysis protocol in November 2019. This study compared patients managed with the two protocols, using propensity score analysis to overcome the potential weaknesses of a retrospective study. The primary outcome was the frequency of preterm birth before 34 weeks of gestation before and after the protocol was revised. The secondary outcomes were frequency of neonatal intensive care unit admission and frequency of neonatal chronic lung disease. Results: The study population consisted of 82 patients managed by the long-term tocolysis protocol and 56 patients managed by the short-term tocolysis protocol. After propensity score-weighted adjustment, the median durations of intravenous ritodrine administration in the long-term and short-term protocols were 18 days and 3 days, respectively. Differences were not detected between the long-term and short-term protocols in terms of the frequency of preterm delivery before 34 weeks of gestation [23.7 % vs 21.6 %, risk ratio (RR) 0.91, 95 % confidence interval (CI) 0.47–1.77], frequency of neonatal intensive care unit admission due to preterm birth (49.5 % vs 39.3 %, RR 0.79, 95 % CI 0.53–1.19) and frequency of neonatal chronic lung disease (4.4 % vs 9.2 %, RR 2.07, 95 % CI 0.51–8.48). Conclusion: Using propensity score analysis, changing from the long-term tocolysis protocol to the short-term tocolysis protocol for the management of preterm labour after 26 weeks of gestation did not have a negative effect on the frequency of preterm birth or neonatal prognosis.